Exploring pharmacists' perspectives on preparing discharge medicine lists: A qualitative study - Helena Gjone; Gemma Burns; Trudy Teasdale; H. Laetitia Hattingh (Elsevier, 2023)
Background: Hospital pharmacists play an important role in the discharge process, including conducting medicine reconciliation, counselling patients or carers, and generating discharge medicine lists. These contribute to medicine handover at transition of care from hospital discharge. However, pharmacists face numerous barriers to providing comprehensive discharge services. Aim: To gain a deeper understanding of the hospital pharmacists discharge processes. Method: Qualitative study design was used to explore pharmacists' experiences and opinions regarding (1) the use of technology and software to prepare patient discharges, (2) involvement of pharmacy assistants in discharge processes, and (3) challenges and facilitators in preparing patient discharges. An independent researcher conducted semi-structured interviews with 15 pharmacists between 29 October and 22 December 2021 (mean interview 21 min). Interview transcriptions were analysed using thematic analysis. Results: Interviews revealed four overarching themes: patient safety, staff involved in discharge processes, discharge handover procedures and electronic health software. Barriers to completing discharges included staff workloads, poor medical record software integration and lack of advanced discharge notice. Good communication between pharmacists and other clinicians, including the presence of a discharge nurse on the inpatient unit, made discharges more efficient, and most pharmacists favoured utilisation of pharmacy assistants in preparing discharge medicine lists. Conclusion: Poor integration between medical software systems negatively impacts pharmacists' ability to complete discharge medicine lists. Pharmacists require advance notice of upcoming discharges to effectively prioritise high workloads, while increased utilisation of trained pharmacy assistants may facilitate discharge workflows.